2018
DOI: 10.3390/ijms19102854
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Distribution of Fenoxanil-Loaded Mesoporous Silica Nanoparticles in Rice Plants

Abstract: Mesoporous silica nanoparticles (MSNs) can be used as carriers to deliver pesticides into plants, which is considered to be one method of improving the efficacy of pesticide usage in agricultural production. In the present work, MSNs with an average diameter of 258.1 nm were synthesized and loaded with Fenoxanil. The structure of the nanocarriers was observed by scanning electron microscopy. The loading content of Fenoxanil-loaded MSNs was investigated. After rice plants in a hydroponic system were treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Furthermore, a small amount of Pro could be transported from the roots to the leaves in plants, and the Pro concentration of PD@ZIF-8 (190.6 ± 14.6 μg/g) was slightly higher than that of Pro (159.7 ± 2.6 μg/g). These results showed that the ZIF-8 nanoparticles can carry substances that were difficult for the plant to uptake, such as some pesticides, especially nonsystemic pesticides, which may improve the content distribution of active substances in plants and effective utilization rate …”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Furthermore, a small amount of Pro could be transported from the roots to the leaves in plants, and the Pro concentration of PD@ZIF-8 (190.6 ± 14.6 μg/g) was slightly higher than that of Pro (159.7 ± 2.6 μg/g). These results showed that the ZIF-8 nanoparticles can carry substances that were difficult for the plant to uptake, such as some pesticides, especially nonsystemic pesticides, which may improve the content distribution of active substances in plants and effective utilization rate …”
Section: Resultsmentioning
confidence: 93%
“…The use of synthetic pesticides (including herbicides, insecticides, fungicides, and other agrochemicals) in agriculture has increased steadily to 3.5 billion kg/year of active ingredient, whereas the actual utilization of biological target uptake is <0.1% . This is because most pesticides are directly lost to the environment through leaching, evaporation, and drifting during spraying or are degraded by light, temperature, and microorganisms. , Moreover, several nonsystemic pesticides are not absorbed or only small amounts are absorbed by the plant, which significantly reduces the efficiency rate of pesticides . All these problems will gradually lead to environmental pollution and ultimately threaten human health.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Active molecules may also be entrapped inside NPs to protect host molecules from unexpected degradation. For example, mesoporous silica nanoparticles (MSN) have demonstrated potential for delivering prochloraz in cucumber (Zhao et al 2018) and fenoxanil in rice (Zhu et al 2018).…”
Section: Mechanisms Of Nano-delivery Systems Loadingmentioning
confidence: 99%
“…The yield and quality of grain have become primary problems to be solved in agriculture all over the world 1–3 . In grain production, pesticides are used to reduce the damage of plant diseases, pests and weeds 4–6 . However, the traditional pesticide formulations, such as emulsifiable concentrate, wettable powder, suspension concentrate and water‐dispersible granule, have low utilization rate of active ingredients, resulting in high control cost, pest resistance, high toxicity to mammals and environmental pollution 7–10 …”
Section: Introductionmentioning
confidence: 99%